Spatial-temporal analyses of Eastern Pacific green turtles (Cheloniamydas/Chelonia agassizzii) foraging as mixed stock in Gorgona NNP, Colombian Pacific Ocean (2012)
Gorgona Island represents a characteristic foraging ground for the green and black turtles (Chelonia mydas/agassizii) that connects rookeries in the Eastern Tropical Pacific Ocean (ETPO). We used mitochondrial DNA Control Region sequences of 176 individuals from a seven years sampling (2005 - 2011) at Gorgona foraging ground (FG). Control Region sequences (940bp) revealed the presence of twenty-three haplotypes, with high haplotype (h) and low nucleotide (Pi) diversities of h = 0.7869 más/menos 0.0185 and Pi = 0.006576 más/menos 0.003472 31 respectively. At spatial level, we identified two Stock Management Units (SMU) in the Eastern Pacific. We determined that orphan Gorgona FG haplotypes came from three different phylogeographic clades. At temporal level, we found substantial variations in genetic diversity. Changes in the haplotypes frequency and unique annual and, seasonal haplotypes. There are temporal variations in the contribution by differential recruitment from different pacific rookeries, where Gorgona FG comprised mostly of animals from the Galapagos rookery (59-93%). Seasonal variations of connectivity in the suitable habitat were found for the species. The suitable habitat models allowed us to define that Sea Surface Temperature (SST), nitrates, dissolved oxygen and salinity have a crucial role in the Pacific distribution of the green and black turtles. We highlighted Gorgona FG is part of the Eastern Pacific SMU with connectivity based on genetic and suitable habitat analyses. Temporal genetic variations could be useful for the conservation and management strategies of the green and black turtles recruited from distant rookeries. It is necessary to implement mainly more sampling efforts at spatial and temporal levels, satellite telemetric analyses, nuclear genetic markers as complement to this study to reinforce trans-national conservation programs and to protect the ETPO corridor in international waters throughout the eastern Pacific managed by non-governmental organizations.